Enhancing Healthcare Access: Drone-based Delivery of Medicines and Vaccines in hard-to-Reach Terrains of Northeastern India - Sumit Aggarwal; Sivarman Balaji; Prakamya Gupta; Nupur Mahajan; Kuldeep Nigam; Khangembam Jitenkumar Singh; Balram Bhargava; Samiran Panda (Preventive Medicine: Research & Reviews, 2024)
Background: Ensuring efficient healthcare access in a geographically diverse country like India poses significant challenges, particularly in challenging terrains. Conventional transportation methods often encounter difficulties due to inadequate infrastructure and adverse climatic conditions, resulting in delays in medical supplies. This study aimed to assess the viability of drones for transporting various types of medical supplies across diverse geographical landscapes, also evaluating their impact on transportation time, covered distance, weight carrying capacities and safety of medical supplies. Materials and Methods: The study spanned 4 months across 19 healthcare centres across Manipur and Nagaland. Different types of drones were used for the transportation of vaccines, medications and surgical items across these centres covering terrains such as flatlands, valleys, foothills, islands and hills. Results: Drones were able to successfully transport the medical supplies maintaining the essential temperatures and integrity of the samples. Further, drone-based supplies significantly reduce the delivery time compared to conventional road-based delivery mechanisms. Conclusion: The present study demonstrates the potential application of drones for the delivery of healthcare supplies in remote areas. Despite the logistical challenges, drones offer a time-efficient alternative for medical supply delivery. However, there is a need for further research and logistical infrastructure development in the current field.